Pendidikan Mental Health Upaya Meningkatkan Kesehatan Mental Remaja di SMA Negeri 2 Banguntapan - Hodiri Adi Putra; Norra Hendarni Wijaya (Yayasan Literasi Sains Indonesia, 2025)
Mental health in adolescents is no longer a taboo issue, especially among teenagers, as this period is a unique transition period where individuals experience physical and psychological changes from childhood to adulthood. Healthcare services for adolescents must be addressed in two aspects: treating them as children with inherent rights, including guardianship provisions, and treating them as individuals approaching adulthood with several accompanying rights. Healthcare services for adolescents are complex and involve many health and non-health professionals. Incorrect or inappropriate treatment can have unpleasant consequences and even be detrimental to adolescent health. The purpose of this activity is to increase students' knowledge and understanding and raise awareness of the importance of maintaining mental health. This activity method involves socializing mental health with students. The results of the activity indicate an increase in students' knowledge and understanding of mental health. It is recommended that further activities be provided to foster full awareness and habits in maintaining mental health among adolescents.